Knowledge of undergraduate dental students regarding management of caries lesions - Anahita Jablonski-Momeni; Heike Korbmacher-Steiner; Alexa Temming; Pia Wernke; Monika Heinzel-Gutenbrunner; Rainer Haak; Felix Krause (Nature Publishing Group, 2022)
Abstract Objectives Understanding of lifelong control of disease processes associated with caries and its management is an essential part of dental education. This study evaluated the dental students' knowledge of caries diagnosis and management using the International Caries Classification and Management System (ICCMS). Methods A survey was conducted among undergraduate dental students at two dental schools, attending the sixth (centre 1) and seventh semester (centre 2), respectively. Medical histories, clinical images and radiographs of 12 patients were compiled as anonymous cases. For each case, a specific lesion was to be assessed. In addition, the students should determine the patient's caries risk and select a treatment option. An expert report (consensus decision) was used as the reference standard. For statistical analysis, kappa statistics and binomial tests were used. Results A total of 46 students participated in this study. The percentage of agreement of responses to the reference was: centre 1: 40.7-51.3%, centre 2: 57.9-67.9%. The corresponding Kappa values were: centre 1: 0.073-0.175, centre 2: 0.315-0.432. Overall, students tended to underestimate the codes compared to the reference standard (p < 0.001). Conclusion Introducing systematic content about caries diagnosis and management such as ICDAS and ICCMS in the learning objectives of undergraduate dental students can be proposed. However, in order to improve diagnosis and enable a more reliable choice of treatment options, attention should also be given to the way they are didactically taught.